Phenomenon-Based Teaching and Learning through the Pedagogical Lenses of Phenomenology: The Recent Curriculum Reform in Finland - Symeonidis, Vasileios; Schwarz, Johanna F. (University of Lower Silesia, 2016)
This paper aims to explore the phenomenon-based approach in teaching and learning, through the pedagogical lenses of phenomenology, the philosophy of phenomena. The phenomenon-based approach has informed the new core curriculum for basic education in Finland, which has officially introduced multidisciplinary learning modules as periods of phenomenon-based project studies. In this paper, we discuss how the specific approach is integrated into the curriculum, its theoretical grounding and its connections to constructivism. We also explore its implications for teaching and learning from a phenomenological perspective. The paper concludes that the responsive relation between teaching and learning is essential when our purpose is educational. Students are part of the learning process, but they do not necessarily initiate it; similarly, teachers cannot fully instruct it. Thus, we need to make meaning of the space between teaching and learning, in an effort to reclaim learning for pedagogy. Niniejszy artykuł omawia ujmujący całościowe zjawiska model uczenia się i nauczania (phenomenon-based approach) z pedagogicznej perspektywy fenomenologii, czyli filozofii tego, co bezpośrednio dane. Prezentowane podejście stało się fundamentem nowej podstawy programowej dla szkół podstawowych w Finlandii, która oficjalnie wprowadza multidyscyplinarne moduły kształcenia przewidujące okresy realizacji projektów poświęconych całościowym zjawiskom. W artykule pokazujemy, jak to konkretne podejście wbudowane zostało w program nauczania, jakie jest jego teoretyczne zakotwiczenie i jak powiązane jest ono z konstruktywizmem. Zgłębiamy również jego implikacje dla nauczania i uczenia się w optyce fenomenologicznej. Na zakończenie przedstawiamy wniosek, że kluczowym czynnikiem w osiąganiu celów edukacyjnych jest właściwe sprzężenie między nauczaniem a uczeniem się. Uczniowie stanowią czynnik procesu uczenia się, ale niekoniecznie sami proces ten inicjują; nauczyciele, podobnie, nie mogą go w pełni samodzielnie przeprowadzić. A zatem aby przywrócić uczenie się pedagogice, musimy zrozumieć przestrzeń między nauczaniem a uczeniem się.